1987
DOI: 10.1007/bf00017995
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of repetitive elements in several Cucurbita species

Abstract: About 1.3×10(5) copies of a tandemly arranged, 351 base pair element constitute from 4 to 8% of the Cucurbita pepo genome. A homologous, high copy number repetitive element is present in the genomes of C. moschata and C. foetidissima, but not in C. maxima or Cucumis sativus. Array lengths of at least 65 members have been detected for C. pepo, and 140 for C. moschata. The nucleotide sequence of six C. pepo repeat units were determined and each was found to be unique, differing from the others at from 7 to 23 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…To investigate the nucleotide sequences of the 350-bp satellite in comparison to the repeats of C. pepo previously published Leclerc and Siegel 1987) we sequenced several repeats cloned from genomic DNA of C. ficifolia, C. mixta, and C. moschata, and from PCR products of C. fraterna, C. texana, C. sororia, C. maxima, C. lundelliana, and C. pedatifolia. An alignment of all sequences obtained revealed two different types of 350-bp satellite DNA.…”
Section: The 350-bp Satellitementioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the nucleotide sequences of the 350-bp satellite in comparison to the repeats of C. pepo previously published Leclerc and Siegel 1987) we sequenced several repeats cloned from genomic DNA of C. ficifolia, C. mixta, and C. moschata, and from PCR products of C. fraterna, C. texana, C. sororia, C. maxima, C. lundelliana, and C. pedatifolia. An alignment of all sequences obtained revealed two different types of 350-bp satellite DNA.…”
Section: The 350-bp Satellitementioning
confidence: 99%
“…Although the relatively few Cucurbita species are cytologically and morphologically defined (Bates et al 1990), the phylogenetic relationship of the cultivated species is still unclear. Therefore, we have tested the satellite DNAs, 350 bp and 170 bp in length, previously described as occurring specifically in the genus Cucurbita Leclerc and Siegel 1987), to determine whether they are useful in revealing the phylogenetic relationship among the wild species C. lundelliana and C. pedatifolia and the cultivated species C. maxima, C. ficifolia, C. pepo, C. moschata, C. mixta (also described as C. argyrosperma) and the putative progenitors C. texana/C, fraterna (for C. pepo, DeckerWalters 1990) and C. sororia (for C. mixta, Merrick 1990). The aim was to place them into a phylogenetic tree and to compare this tree with those obtained by morphological (Hurd et al 1970), cytological Bemis 1965, 1975), isoenzyme (Puchalsky and Robinson 1990), and chloroplast DNA data (Wilson et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive DNA sequences specific to one genome offer an advantage in this situation in that a phylogeny ofthe genome can be reconstructed without initially considering the complicating factors ofadditional genomes (Kellogg, 1989). These sequences tend to evolve rapidly (Flavell, Rimpau, and Smith, 1977), and sequences specific to genera (Schweizer et al, 1988;Talbert, Patterson, and Chandler, 1989) and even species within genera (Leclerc and Siegel, 1987;Dvorak, Me-Guire, and Cassidy, 1988;Zhao et al, 1989) have been identified. Dvorak, McGuire, and Cassidy (1988) used sequences specific to the A genome ofpolyploid wheat to more precisely define the donor of this genome to T. aestivum and T. timopheevii.…”
mentioning
confidence: 99%
“…This could be tested by analysis of the mRNA structure or IPCR (Inverse Polymerase Chain Reaction) of the flanking sequence DNA. Data on the transcription of other repeated sequences are scarce and few transcribing repeats have been identified (Leclerc & Siegel, 1987). General statements to the effect that repeated sequences are not transcribed are misleading in that no comprehensive studies have been carried out and there is an associated lack of knowledge surrounding function.…”
Section: Discussionmentioning
confidence: 99%